Efficacy of Allium Sativum on Lipid Content in Muscle Tissue of Freshwater Fish Ophiocephalus Striatus (Bloch, 1793) - Dr. S. H. Rathod (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In the present study was to evaluate the effect of garlic Allium sativum on the Lipid content in the muscle tissue of freshwater fish Ophiocephalus striatus. Control group fishes were fed a standard diet and experimental group fishes were feed with standard diet including Allium sativum. Fishes were randomly selected from control and experimental group on days 7, 14, 21 and 28 days anesthetized, and sacrificed for the muscle tissue collection for Lipid estimation by sulfo-phospho-vanillin (SPV) method. In the result a significant decrease in muscle Lipid content in experimental fishes fed by Allium sativum (33.32 ± 0.445, 31.28.18 ± 0.764, 27.32 ± 0.382, 24.16±0.410) compared to the control group (40.45 ± 0.702, 38.73 ± 0.811, 37.33 ± 0.384, 35.28±0.698). Efficacy of dietary Allium sativum induced a statistically significant decline in Lipid concentration in the muscle tissue of Ophiocephalus striatus.